Penerapan Teknologi Informasi dalam Synchronous E-Learning bagi Guru SD Negeri Mustikajaya VII Bekasi - Myrna Dwi Rahmatya; Mochamad Fajar Wicaksono; Hidayat Hidayat; Sri Nurhayati; Riani Lubis (Indonesian Community Service and Empowerment Journal (IComSE), 2021)
This community service aims to improve the ability of SD Negeri Mustikajaya VII Bekasi teachers in utilizing information technology for synchronous e-learning. This needs to be done considering that the COVID-19 pandemic has changed the way people live today. Learning activities that are normally done face-to-face must now be done remotely. One of them is by implementing online learning. The method used for this service is online training using the Zoom meeting application. In this training, the material presented is Google Meet and Google Drive. Participants were asked several questions about Google Meet and Google Drive both before and after the training was held. This is done to determine the increase in the ability of participants in both materials. Participants are also given assignments regarding the two materials to practice the material that has been presented. The results of this activity indicate an increase in the ability of teachers to use Google Meet and Google Drive for online learning purposes.